PENGARUH TINGGI BIBIT KOPI ROBUSTA (Coffea sp.) DENGAN MENGGUNAKAN PUPUK TANIJAU - Roby Roby (Politeknik Pertanian Negeri Samarinda, 2017)
Coffee is one of the many commodities cultivated in the territory of Indonesia. For centuries, coffee has become a trade ingredient, because coffee can be cooked and processed into a tasty beverage. Coffee breeding is the process of making the seeds grow into ready-to-plant seedlings. Fertilization is useful for improving soil conditions, plays an important role in the growth of robusta coffee seedlings and improves the production of quality and yield. Tanijau organic fertilizer is a fertilizer derived from organic materials, trimming plant leaves, crop residues, manure and other compostable organic waste that is very useful to repair soil damage, maintain ecosystems and soil fertility, and improve plant cell network so that plants can grow well and develop.This research was conducted in Agricultural Polytechnic Agricultural Sector of Agricultural Samarinda. The time used in this study is for 3 months starting from February 5, 2017 to May 5, 2017, the purpose of this study is to measure the height of coffee seedlings fertilized using organic fertilizer Tanijau brand and to determine the appropriate dose for the growth of coffee seedlings, this research is 3 treatment as follows: K0 : without fertilizer (control), K1 : Tanijau fertilizer with a dose of 0.5 kg, K2 : Tanijau fertilizer with dose of 1 kg, Furthermore, each treatment on coffee seedlings was repeated 10 times. So the number of plants is 30 plants.The results showed that plant height on treatment of K2 (1 kg / polybag) gave better effect, the largest and most can be seen at week 3, week 6, week 9: 6,56 cm, 15,98 cm and 13.5 cm. The exact dose used in this study is the treatment of K2 with a dose of 1kg / polybag